2008
DOI: 10.1121/1.2822883
|View full text |Cite
|
Sign up to set email alerts
|

Temporal weights in the level discrimination of time-varying sounds

Abstract: To determine how listeners weight different portions of the signal when integrating level information, they were presented with 1-s noise samples the levels of which randomly changed every 100 ms by repeatedly, and independently, drawing from a normal distribution. A given stimulus could be derived from one of two such distributions, a decibel apart, and listeners had to classify each sound as belonging to the "soft" or "loud" group. Subsequently, logistic regression analyses were used to determine to what ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
73
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(85 citation statements)
references
References 25 publications
10
73
1
Order By: Relevance
“…Higher weights have been observed for the temporal portion at the beginning of the sound, showing that the first part contributes more strongly to the perceived loudness of the sound than does the middle portion of the sound. To a weaker extent, a recency effect has also been observed; that is, higher perceptual weights are placed on the ending portion of the sound than on the middle portion (Dittrich & Oberfeld, 2009;Pedersen & Ellermeier, 2008). This weighting pattern differs from that of an ideal observer, who would apply identical weights to all temporal portions of a sound (Berg, 1989) if each element provided the same amount of information concerning the correct response, as was the case in the experiments above.…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…Higher weights have been observed for the temporal portion at the beginning of the sound, showing that the first part contributes more strongly to the perceived loudness of the sound than does the middle portion of the sound. To a weaker extent, a recency effect has also been observed; that is, higher perceptual weights are placed on the ending portion of the sound than on the middle portion (Dittrich & Oberfeld, 2009;Pedersen & Ellermeier, 2008). This weighting pattern differs from that of an ideal observer, who would apply identical weights to all temporal portions of a sound (Berg, 1989) if each element provided the same amount of information concerning the correct response, as was the case in the experiments above.…”
mentioning
confidence: 70%
“…The same value of ΔL/2 = 0.5 dB was subtracted from each segment on a soft trial, so that the mean level for these trials was μ S = 59.5 dB. Although the estimation of perceptual weights would be possible without a difference in mean level, we introduced this difference in level mainly to make the task easier for the participants and also to be compatible with previous experiments (e.g., Berg, 1989;Pedersen & Ellermeier, 2008). To avoid overly loud or soft sounds, the range of levels was restricted to μ ± 2.5 SD.…”
Section: Stimuli and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Pedersen and Ellermeier [69] and Oberfeld [70] have shown that the beginning of broadband noise contributed significantly more to the overall loudness perception than portions in the temporal center or end. So far, the underlying mechanisms are not completely understood.…”
Section: Limitations Of the Modelsmentioning
confidence: 99%